Традиційна пам’ять та єврейська культура: календарні паремії у сефардів - Тамір, А. (Народна творчість та етнографія, 2008)
The folklore of the holidays, belongs to “traditional memory" which is a component of the collective memory. This paper is based on 300 Judeo Spanish proverbs which deal with the holiday cycle. Holiday proverbs are not used only during the actu¬al holidays, but through all the year as a metaphor for human situations or traits. I divided those proverbs three groups: (a) The connection to the holiday is irrevocable, (b) the connection is not essential, (c) those that are barely connected. The proverb expresses simultaneously, the voice of the individual, the voice of the Jewish culture in general, and in particular, the voice of the ethnic group, (Sephardic Jews). Traditional memory, as a part of collective memory may complete and overlap it, but may also contradict it.